Short DNA/RNA heteroduplex oligonucleotide interacting proteins are key regulators of target gene silencing. Issue 9 (30th April 2021) - Asada, Ken; Sakaue, Fumika; Nagata, Tetsuya; Zhang, Ji-chun; Yoshida-Tanaka, Kie; Abe, Aya; Nawa, Makiko; Nishina, Kazutaka; Yokota, Takanori
Abstract: Antisense oligonucleotide (ASO)-based therapy is one of the next-generation therapy, especially targeting neurological disorders. Many cases of ASO-dependent gene expression suppression have been reported. Recently, we developed a tocopherol conjugated DNA/RNA heteroduplex oligonucleotide (Toc-HDO) as a new type of drug. Toc-HDO is more potent, stable, and efficiently taken up by the target tissues compared to the parental ASO. However, the detailed mechanisms of Toc-HDO, including its binding proteins, are unknown. Here, we developed native gel shift assays with fluorescence-labeled nucleic acids samples extracted from mice livers. These assays revealed two Toc-HDO binding proteins, annexin A5 (ANXA5) and carbonic anhydrase 8 (CA8). Later, we identified two more proteins, apurinic/apyrimidinic endodeoxyribonuclease 1 (APEX1) and flap structure-specific endonuclease 1 (FEN1) by data mining. shRNA knockdown studies demonstrated that all four proteins regulated Toc-HDO activity in Hepa1–6, mouse hepatocellular cells. In vitro binding assays and fluorescence polarization assays with purified recombinant proteins characterized the identified proteins and pull-down assays with cell lysates demonstrated the protein binding to the Toc-HDO and ASO in a biological environment. Taken together, our findings provide a brand new molecular biological insight as well as future directions for HDO-based disease therapy.